Effectiveness of Laws Related to Medical Negligence in Bangladesh - Mohammad Hossain (Lex Publica, 2022)
Abstract Medical negligence is a violation of the rights to health and life perpetrated by members of the medical professional group entrusted with preserving those rights. Because of increased issues related to medical negligence, numerous countries have introduced new legislation and established independent courts to enhance their healthcare laws. Sadly, medical negligence and malpractice are an issue in Bangladesh in the lack of elaborate or specific rules. In Bangladesh, many laws include numerous legal obligations for health professionals but are not adequately established. As a result, medical negligence and malpractice are causing substantial social consequences that neither the government nor the society expected or condoned. Given the problems and consequences, the goal of this study is to provide a depth elaboration of medical negligence, analyse the laws that currently exist in Bangladesh regarding medical negligence and identify the significant weaknesses in those laws, and, finally, make some recommendations for how Bangladesh can take practical steps toward preventing violations of patients’ rights to health care. Abstrak Kelalaian medis adalah pelanggaran terhadap hak atas kesehatan dan kehidupan yang dilakukan oleh anggota kelompok profesi medis yang dipercayakan untuk menjaga hak-hak tersebut. Karena meningkatnya masalah terkait kelalaian medis, banyak negara telah memperkenalkan undang-undang baru dan membentuk pengadilan independen untuk meningkatkan undang-undang perawatan kesehatan mereka. Sayangnya, kelalaian medis dan malpraktik menjadi masalah di Bangladesh karena kurangnya aturan yang rumit atau spesifik. Di Bangladesh, banyak undang-undang memasukkan banyak kewajiban hukum bagi profesional kesehatan tetapi tidak ditetapkan secara memadai. Akibatnya, kelalaian medis dan malpraktik menyebabkan konsekuensi sosial yang substansial yang tidak diharapkan atau dimaafkan oleh pemerintah maupun masyarakat. Mengingat masalah dan konsekuensinya, tujuan dari penelitian ini adalah untuk memberikan penjelasan mendalam tentang kelalaian medis, menganalisis undang-undang yang saat ini ada di Bangladesh mengenai kelalaian medis dan mengidentifikasi kelemahan signifikan dalam undang-undang tersebut, dan, akhirnya, membuat beberapa rekomendasi untuk bagaimana Bangladesh dapat mengambil langkah praktis untuk mencegah pelanggaran hak pasien atas perawatan kesehatan.